1996
DOI: 10.1111/j.1651-2227.1996.tb13909.x
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and pathogenesis of Attention‐deficit Hyperactivity Disorder (ADHD): significance of prematurity and perinatal hypoxic‐haemodynamic encephalopathy

Abstract: Attention-deficit Hyperactivity Disorder (ADHD), defined as a disorder of awareness with impulsivity, has lately been characterized as a dysfunction of the striatum (neostriatum = globus pallidus + putamen). This structure is in a unique position of contextual analysis and samples information samples information from almost the entire cortex through its spiny neurons. The etiology is heterogeneous, with genetic as well as lesional factors. Among the latter, pre- and perinatal events are prominent. Advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
1
13

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(144 citation statements)
references
References 38 publications
6
124
1
13
Order By: Relevance
“…However, if part of the cognitive deficit associated with ADHD is due to nongenetic factors such as perinatal environmental influences, 51 then adjusting for IQ might remove some of this nongenetic effect in the ADHD group proportionally more than in the non-ADHD group. This may be especially important for selective attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if part of the cognitive deficit associated with ADHD is due to nongenetic factors such as perinatal environmental influences, 51 then adjusting for IQ might remove some of this nongenetic effect in the ADHD group proportionally more than in the non-ADHD group. This may be especially important for selective attention.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 We recognise that ADHD has multiple causes, both genetic and environmental. The contribution of the DAT1 gene as one of multiple genetic factors is the focus of this study, but we do not discount other genetic factors (such as the contribution of the DRD4 gene) or nongenetic factors, such as the effects of fetal distress on brain anatomy and function, as proposed by Lou 51 and others. These factors may differentially affect the various components of attention.…”
mentioning
confidence: 99%
“…[38][39][40][41] The mechanism of how tobacco smoke affects the fetal brain remains unclear, 6,33 but it has been hypothesized that perinatal events resulting in hypoxia may affect brain development and lead to ADHD. 11,42,43 Such risk factors include threatened abortion, threatened preterm labor, preeclampsia, prematurity, intrauterine growth retardation, low Apgar scores, and fetal distress. 35,44,45 Our study contradicts some of these findings in that we found no association with acute events around delivery except for the rare event of cord prolapse in girls, also suggested in a recent study.…”
Section: Discussionmentioning
confidence: 99%
“…(50) Konarska et al (51) reported that regional deficits in the frontal lobe, particularly in the anterior cingulate and the orb to the frontal cortex, consistently delineate subjects with central nervous system disorders from the general population. We hypothesize that mitochondrial dysfunction may be related to CNS damage in sepsis.…”
Section: Discussionmentioning
confidence: 99%